ELISS compliant IPPT training system (data analysis and gamification focus) - Gong, Hai (Nanyang Technological University, 2022)
Individual Physical Proficiency Test (IPPT) is an important assessing component for National Service (NS) training. It is crucial to make sure the testers conform to the IPPT protocols. Testers also would like to know how to improve on their body postures. With the help of Bluetooth Low Energy (BLE) device integrating with sensors, we can analyze the data provided by the sensors and give some feedback on the conformance. This project aims to develop a motion sensor-based system to emulate the requirement of the ELISS IPPT system used by SAF, with targeting on Push-up and Sit-up station, for Android platform using Bluetooth Low Energy as a communication protocol between the central hub and motion sensors. This project focus on the data analysis and gamification aspect.